Heidegger & the political : dystopias - Beistegui, Miguel de, 1966- (Thinking the political., 1998)
Opening with a sensitive discussion of the controversy of the Heidegger 'affair', Miguel de Beistegui examines key themes in Heidegger's philosophy, linking this throughout with the more political public Heidegger.